LIFE PERSPECTIVES OF PERSONALITY AKMEPERIOD IN THE CONTEXT OF PSYCHOLOGY OF LIFE CREATION - Yamnytsky, Vadym (PSYCHOLOGICAL JOURNAL, 2018)
The article deals with the general directions of realization of life perspectives in the acmeperiod of the person from the standpoint of the concept of development of life creation activity. The theoretical analysis of the current state of the problem of life perspectives, which is included in the scope of the problems of psychology of the person's life path, is carried out. The life perspective in general is understood as a dynamic mental entity, the image of the desired and conscious future life as possible, subject to the achievement of certain goals, the combination of moral-ideological, value-oriented and activity-behavioral self-determination. It is determined that from the standpoint of the psychological and pedagogical approach early youth can be considered a period of psychological readiness to determine life perspectives. The socio-psychological approach considers the formation of life perspectives on the basis of a consistent, individual system of value orientations. The timing modalities of the life perspective are the psychological past, the present and the future, which is determined by the richness of events and the extent of their realization. Psychological readiness for the development of life prospects is mostly determined by the peculiarities of cognitive development of self-consciousness and associated with the mechanisms of reflection and processes of self-knowledge and self-determination. The leading approaches to the definition of age-specific features of the formation and realization of life perspectives from the positions of acmepsychology (acme-model, environment and conditions of acmeologization) and psychology of life creation activity of the personality (phenomenology, types of activity, factors) are outlined. The conceptual space of acmeological and life creation approaches to the time modalities of personality activity is revealed, the space of their intersection is outlined. The sensational period of formation and implementation of life perspectives is determined. The analysis of the content and conceptual space of the acmeperiod of personality has allowed to assert that the preconditions (psychological readiness) for the creation of life perspectives arise in youth, in the period of early adulthood, in the majority, they are outlined, understood and specified. And during the middle age, the most favorable conditions for their realization and implementation are created. The correspondence of life perspectives to the stages of personal development in the acmeperiod in the context of the psychology of personality creation is analyzed. It consists in the gradual convergence of stages of personality maturity and can be expressed as a specific movement: realization in the full scope of the purposeful mode of being and the transition to the meaning mode of being in the world. It is in the latter person that transformed into a subject of his own life-creation, becomes able to fully realize his own potentials, to understand and to realize life perspectives.